Questionable prospective effects of self-esteem on anxiety and academic self-efficacy: a simulated reanalysis and comment on Cao and Liu (2024) - Sorjonen, Kimmo; Melin, Bo (Frontiers in Psychology, 2025)
ObjectivesThe objective of the present simulated reanalysis was to scrutinize the conclusion by Cao and Liu that self-esteem can protect against anxiety and promote academic self-efficacy.MethodWe simulated data to resemble the data used by Cao and Liu. We used triangulation and fitted complementary models to the simulated data.ResultsWe found contradicting decreasing and increasing effects of initial self-esteem on subsequent change in anxiety and academic self-efficacy. These divergent findings suggested that it is premature to assume a protective effect of self-esteem on anxiety and an enhancing effect on academic self-efficacy and the conclusions by Cao and Liu in this regard can be challenged.DiscussionIt is important for researchers to be aware that correlations, including adjusted cross-lagged effects, do not prove causality in order not to overinterpret findings, something that appears to have happened to Cao and Liu. We recommend researchers to triangulate by fitting complementary models to their data in order to evaluate if observed effects may be due to true causal effects or if they appear to be spurious.